PENGARUH LATIHAN KELENTUKAN DINAMIS DAN STATIS TERHADAP GERAK SPLIT DAN TINGGI TENDANGAN PADA SISWA PSHT RANTING PACIRAN - Yoyok Priyo Susanto; Supriyadi Supriyadi; Olivia Andiana (Jurnal Sport Science, 2018)
Abstract In the study conducted a proper exercise to improve the ability of students, especially on the motion of split and high kicks, as the researcher's guidance to practice split and high kicks using dynamic and static exercise drill methods, research design in research using pre experiment method that is using one group pretest and postest, split is a motion of the form stretching the legs as wide as possible with the possession of good split motion will greatly affect the comfort of motion when the practice movement there are 2 kinds of split motion that is split front and side split. Split front movement is stretching your legs forward and backward, split aside stretching both legs to the left and right side. Kick motion is an attacking movement in pencak silat required a good split motion split to get a good kick results, Kick motion is an attacking movement in martial arts required a good split motion split to get a good kick results = 0,000 (0,000 < 0,05) on split side = 0,000 (0,000 < 0,05) at the kick height of A = 0,000 (0,000 < 0,05) at the kick height of T = 0.001 (0.000 <0.05) Dynamic cultivation exercises and static formation can enhance split and high kick motion capabilities in which the effect is muscle shape resulting in a wide range of motion split and kicker heights.Key Word: Elasticity, split motion, high kick